Investigation on quality of thin concrete cover using mercury intrusion porosimetry and non-destructive tests - EDDY, Liyanto; MATSUMOTO, Koji; NAGAI, Kohei; CHAEMCHUEN, Piyaphat; HENRY, Michael; HORIUCHI, Kota (Journal of Asian Concrete Federation, 2018)
Mercury intrusion porosimetry test was carried out to investigate the quality of thin concrete cover. Specimens with different water-to-cement ratios were prepared and exposed to different environmental conditions. The results show that the pore structure of the cover is coarser than that of the center portion when the cover is insufficient. With thinner cover, the pore structure becomes coarser. With decreasing water-to-cement ratio, the pore structure becomes finer, and the difference in the pore structure between the cover and the center portion becomes smaller. If the cover is insufficient, not only the distance needed for substances to reach the bar becomes shorter, but also the pore structure becomes coarser. At 91 days, the pore structures of outdoor specimens are almost the same as those of indoor specimens although the exposure conditions are different. To investigate the applicability of the air permeability test and electric resistivity test to evaluate the cover quality when the cover is insufficient, specimens with different water-to-cement ratios and cover depths were prepared. A combination of the air permeability test and electric resistivity test roughly pointed out the poor quality of the insufficient concrete cover and is a useful technique to evaluate the concrete cover in real structures.